Study on the Reasons Affecting Startup Failures, Diversification Strategy in Kerala - et.al, Dr Antony George, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As in the current scenario, the startups play a pivotal role and has a huge influence on the promotion of economic growth. With the perceived anticipation by the authorities on the significant effect, a startup firm has on the economy as a whole using various affirmative factors as such as the job creation, economic development, meriting to the technological upgradation and many more. There has been a significant attempt to promote entrepreneurship through establishment and support of various incubation centres. But despite the reception appreciated towards its development, the failure rates of the founded startups are at an alarming rate. This research paper aims to outline the various factors concerning the startup failures; and the diversification strategy adopted by the startup founders in the attainment of their objectives and the extent to which it has merited in its objective attainments.